Reducing door-to-reperfusion time in acute stroke endovascular therapy using magnetic resonance imaging as a screening modality. (12th February 2020) - Sakamoto, Yuki; Suzuki, Kentaro; Abe, Arata; Aoki, Junya; Kanamaru, Takuya; Takayama, Yohei; Katano, Takehiro; Kutsuna, Akihito; Suda, Satoshi; Nishiyama, Yasuhiro; Nito, Chikako; Kimura, Kazumi
Abstract : Background: The feasibility of performing MRI first for patients with suspected hyperacute stroke in real-world practice has not been fully examined. Moreover, most past studies of reducing door-to-reperfusion time (DRT) in endovascular treatment (EVT) were conducted using CT. The aim of this study was to evaluate the feasibility of an MRI-first policy and to examine the effects of a quality improvement (QI) process for reducing DRT using MRI. Methods: From January 2013 to December 2018, consecutive patients with acute stroke who came to hospital directly and were treated with emergent EVT were prospectively enrolled into the present study. In principle, MRI was performed first for patients with suspected acute stroke. A step-by-step QI process for decreasing DRT was adopted during this period. Time metrics for EVT were compared between specific time periods. Results: A total of 180 patients (71 women; median age 76 years (range 69–64); National Institutes of Health Stroke Scale score 17 (range 10–23)) were included in the present study. More patients in the late phase were managed with the MRI-first policy (p<0.001). DRT (199 min in Phase 1, 135 min in Phase 2, 129 min in Phase 3, and 121 min in Phase 4, p<0.001) was significantly reduced across the phases. The percentage of patients with DRT <120 min increased significantly across time periods (p<0.001). Symptomatic intracerebral hemorrhage did not increase across phases (p=0.575). Conclusion: An MRI-first policy was feasible, and DRT decreased considerably with a step-by-step QI process. This process may be applicable to other hospitals.